1997
DOI: 10.1074/jbc.272.38.23572
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein Mediates Selective Uptake of High Density Lipoprotein Cholesteryl Esters by Human Adipose Tissue

Abstract: We have determined the role of cholesteryl ester transfer protein (CETP) in selective uptake of high density lipoprotein (HDL)-derived cholesteryl esters (CE) by human adipose tissue, using organ culture or collagenase-digested adipocytes. Incubation of the fresh tissue fragments with HDL containing [ H]CE or125 I-apoprotein (apo) A-I resulted in significant uptake of HDL-CE-derived label. Addition of recombinant CETP (rCETP) increased CE uptake in a dose-response fashion. In contrast, little association of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 41 publications
1
35
1
Order By: Relevance
“…40 Changes in lipoprotein composition 41 can modify the exchange of cholesterol and phospholipids between lipoproteins, or between lipoproteins and cells and inÂŻuence the composition of plasma membranes. These changes could be mediated by cholesteryl Hyperinsulinemia, adipocyte and erythrocyte phospholipids N Zeghari et al ester transfer protein (CETP), which has a role in the selective uptake of HDL cholesteryl esters by human adipocytes, 42 or by phospholipid transfer protein (PLTP). 43 CETP and PLTP activities are elevated in obesity 44 and in insulin resistance 45 as well as the HDL binding to adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…40 Changes in lipoprotein composition 41 can modify the exchange of cholesterol and phospholipids between lipoproteins, or between lipoproteins and cells and inÂŻuence the composition of plasma membranes. These changes could be mediated by cholesteryl Hyperinsulinemia, adipocyte and erythrocyte phospholipids N Zeghari et al ester transfer protein (CETP), which has a role in the selective uptake of HDL cholesteryl esters by human adipocytes, 42 or by phospholipid transfer protein (PLTP). 43 CETP and PLTP activities are elevated in obesity 44 and in insulin resistance 45 as well as the HDL binding to adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that CETP enhances sperm capacitation (15) and facilitates the efflux of CE from cells (16). Additionally, CETP associates with cell plasma membranes where it appears to facilitate CE selective uptake (17).…”
Section: Cholesteryl Ester Transfer Protein (Cetp)mentioning
confidence: 99%
“…In a parallel set of experiments, the selective CE-uptake from HDL 3 was calculated from double-labeled HDL 3 as the difference between [ 3 H]cholesteryl oleate-and 125 Ilabeled lipoprotein [35]. The sum of specific degradation (measured as described above) and specific cell association of 125 I-labeled HDL 3 reflects HDL 3 -holoparticle association.…”
Section: Selective Ce-uptakementioning
confidence: 99%
“…The HDL 3 -band was aspirated and dialyzed against 10 mM NaCl/P i , pH 7.4. [35]. Following separation from the vesicles by ultracentrifugation, the labeled lipoproteins were subsequently labeled with 125 I-Na as described above using N-Br-succinimide.…”
Section: Lipoprotein Labeling Proceduresmentioning
confidence: 99%